The influence of rituximab-containing chemotherapy on HCV load in patients with HCV-associated non-Hodgkin’s lymphomas - Zhou, Xiang; Kriegsmann, Katharina; Giesen, Nicola; Egerer, Gerlinde; Ho, Anthony Dick; Witzens-Harig, Mathias (Annals of hematology, 2017)
Efficacy and safety of rituximab treatment in patients with Hepatitis C virus (HCV) infection associated non-Hodgkin’s lymphoma (NHL) are still disputable. The aim of this study was to evaluate the influence of rituximab-containing chemotherapy on HCV load. Fifty-four patients with both HCV infection and NHL were identified between 2000 and 2016 at our institution. We retrospectively analyzed patients’ demographic characteristics, treatment, and kinetics of HCV load before and after treatment with rituximab-containing chemotherapy. In the total group of 54 patients, 29 (54%) received rituximab. Both HCV load pre rituximab and maximal HCV load post rituximab were available in 16 patients. Overall, we observed no significant difference between HCV load pre rituximab and the maximal HCV load post rituximab (P = 0.19). In a patient who was treated simultaneously with direct-acting antivirals (DAAs) and rituximab-containing chemotherapy, HCV load decreased below the sensitivity level (≤12 IU/ml) during treatment. When regarding the influence of rituximab-containing chemotherapy alone on HCV load, we observed a significant elevation of HCV load (P = 0.04). Rituximab-containing chemotherapy may lead to an increase of HCV load in patients with HCV-associated NHL. However, this finding is based on small patient cohort and should be confirmed in larger clinical trials.